Creative Economy Development in Enhancing Sustainable Tourism Potential in Kutai National Park, East Kalimantan - I Gusti Made Juniarta; Cing Cing Wahyuni; Pungky Dios Purnomo; Apri Kuntariningsih (An International Journal Tourism and Community Review, 2026)
This research investigates the integration of the creative economy as a catalyst for sustainable tourism development within Kutai National Park (KNP), East Kalimantan. Despite its ecological significance as a lowland rainforest and Orangutan habitat, KNP faces stagnation due to a reliance on extractive resources and a lack of diversified tourism products. Employing a qualitative descriptive methodology and SWOT analysis, this study maps the creative potential of the region and evaluates its impact across four sustainability pillars: economic, social, environmental, and institutional. Data were gathered through field observations and in-depth interviews with park authorities, local government officials, and creative entrepreneurs in the buffer zones of Sangatta and Bontang. The findings reveal significant potential in non-timber forest-based culinary arts, modernized ethnic crafts, and digital wildlife storytelling. A critical institutional barrier identified is the "sectoral ego" between conservation authorities and local governments. The study proposes a strategic shift toward a "Green Creative Hub" model, emphasizing that sound governance and institutional synchronization are essential for balancing conservation with economic empowerment. This research provides a roadmap for policy-makers to transition from extractive-based livelihoods to a knowledge-based service economy that preserves the integrity of protected landscapes.